Pengembangan Butir Soal Literasi Kimia pada Materi Kesetimbangan Kimia Kelas XI SMA/MA - Pratiwi Azizzah; Eka Yusmaita (Universitas Negeri Padang, 2022)
This research aims to develop chemical literacy items on chemical equilibrium material that can be used to measure students chemical literacy skills. The items in this study were designed based on four aspects consisting of aspects of content, context, HOLS and attitudes. The preparing chemical literacy items in this study used the Model of Educational Reconstruction (MER) design. The assessment criteria of chemical literacy items carried out by the Subject Matter Expert (SME) include the aspects of content, construct, language and graphics. Chemical literacy questions consist of fifteen questions, it is divided into six themes. The score obtained from the validation process is analyzed using the Facet application. Based on the research result, fifteen chemical literacy questions on chemical equilibrium topics are valid and had a reliability value of 0,92.